HUBUNGAN USIA, JENIS KELAMIN DAN INDEKS MASSA TUBUH TERHADAP DERAJAT KEPARAHAN HEMOROID INTERNA PADA PASIEN HEMOROIDEKTOMI DI RUMAH SAKIT BADAN PENGUSAHAAN BATAM PERIODE 2019-2023 - Fanany, Muhammad Azmi; Susana, Elvita Nora; Nova, Aura Dewi (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2024)
Background : Internal hemorrhoids or in the community better known as hemorrhoids or hemorrhoid is a condition with symptoms that can interfere with the daily activities of the sufferer, the dilation of the veins in the hemorrhoidal plexus is located in the anal area. Risk factors that contribute to the severity of internal hemorrhoids are age, gender and body mass index. Methods : Analytical research method with quantitative cross sectional research design. Data collection technique total sampling with a sample size of 33 respondents. Research results were analyzed with the fisher exact test. Results : The results of the analysis obtained the relationship between age and internal hemorrhoidal severity P = 0.036 (meaningful), the relationship between gender and internal hemorrhoidal severity P = 0.002 (meaningful), the relationship between body mass index and internal hemorrhoidal severity P = 0.023 (meaningful). Conclusion : It can be concluded that there is a relationship between age, gender and body mass index on the degree of internal hemorrhoidal severity in hemorrhoidectomy patients at the Badan Pengusahaan Batam Hospital for the 2019-2023 period.